Existence of positive periodic solutions of several types of biological models with periodic coefficients. (February 2023) - Guo, Ke; Ma, Wanbiao
Abstract: This paper investigates the existence of positive periodic solutions for several types of important biological models with periodic coefficients, including the HIV model with multiple infection stages and general incidence, the epidemic models (such as the SIRS model, the SIRI model, the SEIRS model, etc.) with general incidence. By means of the continuation theorem in the coincidence degree, and the combination of analytical techniques such as constructing appropriate auxiliary functions, we give several classes of explicit sufficient conditions for the existence of positive periodic solutions for these biological models. When these models with periodic coefficients degenerate to the corresponding autonomous cases, our conditions all naturally degenerate to the basic reproduction number is greater than 1. Our results greatly improve and expand the studies in the existing literatures.